Diversity of Cropping Pattern in Bogra - Islam, ABMJ; Shahidullah, SM; Mostafizur, ABM; Saha, A (Bangladesh Rice Journal, 2018)
With a view to document the existing cropping patterns, cropping intensity and crop diversity, a study was carried out over all the upazilas of Bogra agricultural region during 2015-16. A pre-tested semi-structured questionnaire was properly used for this purpose. In the findings it was recorded that 21.88% of net cropped area (NCA) of the region was occupied by the cropping pattern Boro−Fallow−T. Aman. This pattern was found to be distributed over 27 upazilas out of 35. The second largest area, 13.26% of NCA, was covered by Potato−Boro−T. Aman, which was spread over 17 upazilas. A total of 177 cropping patterns were identified in the whole region in this investigation. The highest number of cropping patterns was identified 36 in Nandigram upazila and the lowest was six in Dupchachia and Kahalu upazila of Bogra district. The lowest crop diversity index (CDI) was reported 0.718 in Raiganj upazila of Sirajganj district followed by 0.734 in Kalai of Joypurhat. The highest value of CDI was observed 0.978 in Pabna sadar followed by 0.972 in Bera upazila. The range of cropping intensity values was recorded 183-291%. The maximum value was for Khetlal upazila of Joypurhat district and minimum for Bera of Pabna. As a whole the CDI of Bogra region was calculated 0.966 and the average cropping intensity at regional level was 234%. Bangladesh Rice j. 2017, 21(2): 73-90